PENGARUH MEDIA PEMBELAJARAN AUGMENTED REALITY PADA MATERI KERAGAMAN BUDAYA TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS V SEKOLAH DASAR - Khofifah Shaira Siregar; Waliyul Maulana Siregar; Elvi Mailani; Apiek Gandamana; Putra Afriadi (Universitas Negeri Medan, 2026)
This study aims to determine the effect of using Augmented Reality media on student learning outcomes in Pancasila Education in grade V of SD Negeri 101744 Klambir Village. This study used a quantitative approach with a quasi-experimental design of the nonequivalent control group type. The research sample consisted of two classes, namely class VA as the control class, which received conventional learning methods in the form of lectures and assignments, and class VB as the experimental class, which was given treatment using Android-based Augmented Reality media. Data collection was carried out through pretest and posttest tests, then analyzed using the independent sample t-test. The results showed that there was a significant effect on student learning outcomes after the implementation of Augmented Reality media. Students in the experimental class experienced an increase in learning outcomes of 84.63%, while students in the control class only achieved 72.00%. Based on the results of data analysis, the t-count value was greater than the t-table (4.798 > 2.009) with a significance value (2-tailed) of 0.000 < 0.05. The results of the hypothesis test show that H₀ is rejected and Hₐ is accepted, so it can be concluded that the use of Augmented Reality media in Pancasila Education learning is proven to be effective in improving student learning outcomes.